(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article analyzes the mineralogical state of molybdenum, one of the associated elements in the technological solutions found in uranium deposits, its forms in composition, and extraction technologies. The transition of molybdenum to the technological solution during the hydrometallurgical processing of uranium and the main methods of its separation - extraction, ion exchange, and sorption processes - are considered in detail. The economic and environmental significance of separating molybdenum as a by-product is also emphasized. The article serves to expand the possibilities of complex use of raw materials in the uranium mining industry